Does periodization matter? The effect of different high intensity periodization models on endurance adaptations (2016)
The main purpose of this study was to compare the effects of three different HIT models, balanced for total load but periodized in a specific mesocycle order or in a mixed distribution, on endurance adaptations during a 12-wk training period in well-trained endurance athletes. The authors simulated a preparation period in which athletes in Increasing (INC), Decreasing (DEC) and Mixed (MIX) HIT groups performed training periods that were matched for all features (frequency, total volume, and overall HIT load) except the mesocycle order or distribution of HIT sessions. We hypothesized that the INC HIT organization would be best tolerated and give best overall adaptive effects.